Developing an Islamic investment framework for maritime assets - Abdullah, Adam; Hassan, Rusni; Kassim, Salina (Medwell Journals, 2017)
This paper seeks to develop an Islamic investment framework for maritime assets. Following the recent global financial crisis, the financial performance of international ship-owners has been significantly eroded in the presence of debt-based finance and volatile maritime earnings. Accordingly, this paper seeks to develop an Islamic investment framework for maritime assets based on equity finance in order to provide an alternative to conventional debt-based ship financing. The approach taken analyzes the related theoretical concepts in relation to Islamic investment contracts, the Islamic normative theory of profit, inter-temporal choice and investment, efficiency of resource allocation and the Islamic monetary theory of value. The significance of this study clarifies the underlying theories associated with Islamic investment analysis for maritime assets, and also provides a broader framework for infrastructure funding of other real assets generally.